“Who Am I”: The Role of Character Strength in Self-Awareness Emerging Adulthood - Edy, Dewi Fatmasari; Nurmalitasari, Femmi; Puspitasari, Dwi Nikmah; Ashgarie, Rayza Ilfie Azkya; Nihayah, Nilai Shofy (Universitas Negeri Malang, 2023)
Previous research shows that self-awareness is important for emerging adulthood. Individual knowledge of himself is required, specifically the strength of his character, to increase self-awareness. For this reason, this research shows the role of emerging adulthood character strengths on self-awareness. The research was carried out using a non-experimental quantitative approach with a research design in the form of a survey. Sampling was done using simple random sampling. The measuring instruments used are the Indonesian version of character strength developed by the VIA Institute via the viacharacter.org page formulated by Peterson & Seligman (2004) and the Self-Awareness Outcomes Questionnaire (SAOQ) created by Sutton (2016), which researchers adapted. These two measuring instruments have been proven to be valid and reliable in measuring the selected variables. Data collection was carried out using Google Forms, and a total of 142 participants were used for hypothesis testing. Hypothesis testing using a simple linear regression test shows that character strength plays a significant role in predicting emerging adulthood self-awareness with a predictive power of 64 per cent, and the direction of the relationship between the two is in the same direction. This means that the higher the strength of character, the greater the self-awareness. Thus, it is known that the true potential of emerging adulthood can be maximized if individuals are aware of their character strengths. This is because character strength can be an element in self-exploration and self-understanding. Research suggestions are attached.